LEGALITAS TINDAKAN ABORTUS PROVOCATUS OLEH KORBAN PERKOSAAN - Rochayati, Siti (Faculty of Law, University of Palembang, 2018)
The objective of the study was to analyze and describe the legality of the act of abortion provocatus by rape victims. Research methods ; using the normative juridical method. Results : Rape can be interpreted as coercion of the will of a party to another party, regardless of the rights, interests and willingness of other parties who are forced for the purpose of profit or personal interest for the coercion. The consequences of sexual violence (rape) that befell the victim not only adversely affect his physical endurance, but also his psychological resilience. This psychological impact will be more severe when the victim is then pregnant as a result of the rape. This raises the question of whether abortion should be possible. Approach method used is juridical Normative writing by trying to find the data as much as possible by focusing on the rules that apply and the literature or books related to the issues discussed related to the discussion of the legality of the act of abortion provocatus by rape victims. Abortion is a crime. The law prohibits a woman or other person from assisting in an act of abortion. As in Article 346 of the Criminal Code and Article 75 paragraph 1 of Law No.36 of 2009 on health. However, the provisions of article 75 paragraph 1 there are exceptions, one of them in the case of rape. So u allow abortion with some provisions.